Cuticle fatty acid composition and differential susceptibility of three species of Cockroaches to the Entomopathogenic Fungi Metarhizium anisopliae (Ascomycota, Hypocreales) - Gutierrez, Alejandra Concepción (2015)
Differences in free fatty acids (FFAs) chemical composition of insects may be responsible for susceptibility or resistance to fungal infection. Determination of FFAs found in cuticular lipids can effectively contribute to the knowledge concerning insect defense mechanisms. In this study, we have evaluated the susceptibility of three species of cockroaches to the entomopathogenic fungi Metarhizium anisopliae (Metschnikoff) Sorokin by topical application. Mortality due to M. anisopliae was highly significant on adults and nymphs of Blattella germanica L. (Blattodea: Blattellidae). However, mortality was faster in adults than in nymphs. Adults of Blatta orientalis L. (Blattodea: Blattidae) were not susceptible to the fungus, and nymphs of Blaptica dubia Serville (Blattodea: Blaberidae) were more susceptible to the fungus than adults. The composition of cuticular FFAs in the three species of cockroaches was also studied. The analysis indicated that all of the fatty acids were mostly straight-chain, long-chain, saturated or unsaturated. Cuticular lipids of three species of cockroaches contained 19 FFAs, ranging from C14:0 to C24:0. The predominant fatty acids found in the three studied species of cockroaches were oleic, linoleic, palmitic, and stearic acid. Only in adults of Bl. orientalis, myristoleic acid, c-linolenic acid, arachidic acid, dihomolinoleic acid, and behenic acid were identified. Lignoceric acid was detected only in nymphs of Bl. orientalis. Heneicosylic acid and docosahexaenoic acid were identified in adults of Ba. dubia.